A Cheap Kidney Phantom for Kidney Biopsy - Badeli, Hamidreza; Shadpour, Shahrbanou; Akbarpour , Shahin (Journal of Pediatric Nephrology, 2020)
Percutaneous renal biopsy is the most common method for obtaining renal tissue. In this article, the authors first explained how to make a cheap model of phantom easily by sheep’s kidney in a bowl filled with jelly. Then in the attached video, they showed how to find the ideal site (lower pole of kidney) and in real time, traced biopsy needle from jelly surface to kidney concomitant with ultrasound screen.